Online Writing Community: What Can We Learn from Failure?. (April 2022) - Tang, Eunice; Cheng, Lily; Ng, Ross
Peer feedback or peer review has been promoted in the English writing classroom as an effective strategy to improve writing skills. With the popularity of adopting technology in learning, our research introduced participants to an online writing community (OWC) which incorporates the concepts of peer feedback and collaborative learning as an innovative pedagogy to improve writing skills in an autonomous environment. The OWC was created for students in an English Education programme in a Hong Kong university. However, the attempt was a failure given its low participation and interaction rates. A study was subsequently conducted to understand participants' and non- participants' perception and behaviour towards the learning environment and activity. Data were collected through questionnaires, interviews and reflective journals. Non-participants claimed that lack of time, heavy workloads, the non-compulsory and non-credit bearing nature of the course deterred them from joining the OWC. While participants in the OWC did not concur with the claims, they identified factors which might have accounted for the low interaction rate in the OWC. These included: i) commitment of the OWC members; ii) rapport among the OWC members; iii) interactiveness and spontaneity of the platform; and, iv) ease of use. The results suggest ways that innovative pedagogy could be implemented and enhanced for effective learning in the future.